Luteoporia citriniporia sp. nov. (Polyporales, Basidiomycota), evidenced by morphological characters and phylogenetic analysis - Liu, Zhan-Bo; Yuan, Yuan (Phytotaxa, 2020)
A new poroid wood-inhabiting fungus in the Polyporales, Luteoporia citriniporia sp. nov., is described from Sri Lanka based on morphological and molecular evidence. L. citriniporia is characterized by an annual growth habit; resupinate basidiocarps with lemon yellow pores when fresh becoming buff to clay pink upon drying, a distinct snow white and fimbriate sterile margin, tissues becoming pink in KOH, a monomitic hyphal system, generative hyphae thin- to distinctly thick-walled, usually encrusted with fine yellow crystals, and oblong-ellipsoid to subcylindrical basidiospores measuring 3.4–4.2 × 1.8–2.1 µm. The phylogenetic analysis based on ITS + nLSU rDNA sequences shows that the new species belongs to Luteoporia, forming a monophyletic lineage with strong support (100% BS, 100% BP, 1.00 BPP) and is closely related to L. albomarginata; the lineage groups with Crustodontia chrysocreas, Phlebiporia bubalina and Mycoacia uda. Both morphological and molecular characters confirm the placement of the new species in Luteoporia.